2021
DOI: 10.1002/solr.202100879
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Dimensional Perovskites Heterostructure for Highly Efficient and Stable Perovskite Solar Cells

Abstract: Organic-inorganic hybrid perovskite solar cells (PSCs) have attracted tremendous attention due to their unique optoelectronic properties, power conversion efficiency (PCE), cost-effectiveness, and solution processability. [1][2][3][4][5] Within a few years, the PCE of 3D (3D) perovskite materials based PSCs has rapidly soared from 3.8% to 25.8%, which is comparable with that of the state-of-art monocrystalline silicon solar cells. [6][7][8] However, because of their intrinsic structural characteristics, 3D per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…The perovskite photoactive layer is known to play a critical role in the photovoltaic performance and durability of PSCs. [57] We prepared a series of perovskite thin films following the previously reported two-step methods, [58,59] as illustrated schematically in Figure S1, Supporting Information. In the first step, dimethyl sulfoxide (DMSO) and N, N-dimethylformamide (DMF) mixed in a volume ratio of 1:19 served as the solvent for deposition of the PbI 2 layer in the presence of MAAc in different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite photoactive layer is known to play a critical role in the photovoltaic performance and durability of PSCs. [57] We prepared a series of perovskite thin films following the previously reported two-step methods, [58,59] as illustrated schematically in Figure S1, Supporting Information. In the first step, dimethyl sulfoxide (DMSO) and N, N-dimethylformamide (DMF) mixed in a volume ratio of 1:19 served as the solvent for deposition of the PbI 2 layer in the presence of MAAc in different concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Yang et al (33) used a crosslinking polymerizable propargylammounium (PA + ) on top of the perovskites, while no obvious evidence was shown that 1D perovskites could get into the GBs. Ge et al (44) applied a 1D trimethyl sulfonium lead triiodide into the 3D perovskite; nevertheless, still no obvious evidence showed that the 1D nanoroid could stay at the GBs. Kong et al (35) used 2diethylaminoethylchloride cation to form a 1D perovskitoid as the perovskite growth template, but still no distinct evidence showed that the perovskite would be at GBs.…”
Section: Evidence Of Grain Wrappingmentioning
confidence: 99%
“…A hybrid metal halide perovskite offers favorable optoelectronic properties, including a high absorption coefficient, long carrier lifetimes, color tunability, band gap modulation, and long diffusing lengths, among others. , This has led to its increasing applications in solar cell devices, with certified power conversion efficiency reaching 25.8%. , Moreover, most of the reported perovskite solar cells (PSCs) have been developed using low-temperature solution-processing techniques, and its fabrication has also been demonstrated for a large area. However, stability of PSCs remains a challenge for commercialization and needs to be addressed. , It has been demonstrated that a solution-processable perovskite film contains various defects, which lead to recombination of the charge carrier and, consequently, add to instability of the device. , Various approaches, such as hot casting, anti-solvent dripping, vacuum flash treatment, solvent annealing, dimensional engineering, etc., are being attempted to reduce the defects in the perovskite layer for increasing the stability of the solar cells. Moreover, the introduction of multifunctional organic molecules for the passivation of ionic defects in the perovskite is one of the best known techniques to increase the device performance in terms of power conversion efficiency (PCE) and stability of laboratory-scale and large-area PSCs. ,, The multifunctional additives help to reduce the ion migration and increase the crystallinity of the perovskite. …”
Section: Introductionmentioning
confidence: 99%